Endoplasmic reticulum stress drives proteinuria-induced kidney lesions via Lipocalin 2 - Khalil El Karoui (Nature Portfolio, 2016)
Proteinuria promotes chronic kidney disease progression. Karoui et al. show that proteinuria stimulates overexpression of iron transporting protein lipocalin-2 via Ca2+release-induced ER stress, which leads to tubular apoptosis, and that inhibition of this pathway by PBA delays renal deterioration in proteinuric mice.